REMEDIASI MISKONSEPSI PESERTA DIDIK MENGGUNAKAN MODEl PEMBELAJARAN PREDICT-DISCUSS-EXPLAIN-OBSERVE-DISCUSS-EXPLAIN DI SMP - Alek, Sutrisno; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effectiveness of the PDEODE learning model in conducting remediation of students’ misconceptions on hydrostatic pressure material. Per-experimental design with One Group Pretest-Posttest was employed in this study. The population was all stusents of class VIII in the State Junior High School 1 Siantan. The research sampel was preferred by Intact Group so that it can be obtained Class VIII C, which amounted to 34 student. The research instrument used a diagnostic test which consisted of 6 items in the form of multiple choice with an open reason. The large percentage decreased in the number of students who experienced misconception after being given remediation of misconceptions with the PDEODE model on the material of hydrostatic pressure was 61%. The researcher administered the McNemar test with a significance level of 5% which showed that there had been a significant change in the conception of students after being given remediation activities using the PDEODE model. The PDEODE model was considered very effective for remediation of student misconceptions in the hydrostatic pressure material with an effect size 0,3 with a low category according to the Hattie barometer. As a result, the PDEODE model was considered less effective in reducing the number of misconceptions of students. Kata kunci:Predict Discuss Explain Observe Discuss Explain, Remediation Misconception